A study on the use of three-dimensional dielectric crossed compound parabolic concentrator for daylighting control application - Tian, Meng (2018)
As a low concentration concentrator with a larger acceptance angle and without a tracking requirement, compound parabolic concentrator is regarded as an attractive solution to improve the system performance and reduce the cost of photovoltaic (PV) system, solar thermal system, daylighting and lighting systems, etc. As a typical type of three-dimensional compound parabolic concentrator (CPC), dielectric crossed compound parabolic concentrator (dCCPC) has drawn a significant research attention in these years to explore its angular characteristics in solar collection for concentrating photovoltaics and daylighting control in buildings. This thesis provides a comprehensive study on dCCPC in aspect of daylighting control. The work starts from a general review that provides a detailed introduction of the background of CPC applications in solar energy. Then the fundamental property of dCCPC when it is utilized as skylights for daylighting control is investigated, and the performance of dCCPC is also compared to other types of CPC. With the consideration of actual application, the dCCPC panel should be designed as small as possible to reduce its weight and maintain the optical characters simultaneously. Several criteria relating to the dimension of dCCPC panel are proposed and investigated about their effects on the optical performance of dCCPC, followed by the experiments that are taken for validation. As ray-tracing simulation is the most common way to determine the optical performance of dCCPC which provides accurate result but requires long time to run, the multiple nonlinear regression model and artificial neural network model are put forward in the beginning of the second half of this thesis. The coefficients of determination of these models could reach 0.99 which imply the high accuracy of them. The optical performance of dCCPC can be calculated rapidly by knowing the sun position and sky condition. Afterwards, because the performance of dCCPC can be calculated easily for any time and any location with the mathematical model, a case study was taken to investigate the dCCPC effects on building energy consumption, indoor visual environment and economic benefits. This research proves the potential of dCCPC in terms of daylighting control. As a stationary skylight, the transmittance of it is adjusted automatically depending the sky condition and sun position. It also provides outstanding performance in indoor illuminance distribution. The dCCPC is suggested to be used in the locations with long hot seasons for the purpose of energy saving, and it is suggested for all locations with a view to glare control. For further work, more related criteria are encouraged to be added into the prediction models. The method of manufacturing dCCPC is suggested to be improved. Finally, the asymmetric dCCPC is expected to have high potential in daylighting control as vertical building facade, which is worth to be investigated.